2018
DOI: 10.1515/htmp-2016-0183
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Si3N4 Ceramics and 304 Stainless Steel Brazed Joint with Cu/Ag-Cu/Ti Laminated Filler Metal

Abstract: Si3N4 ceramics and 304 stainless steel were joined by the Cu/Ag-Cu/Ti laminated filler metal. Interfacial microstructure of brazed joint and effect of brazing temperature and thickness of Cu foil on mechanical properties were studied in this paper. Research results showed that the interfacial microstructure of the brazed joint might be 304 stainless steel/TiFe2/Ag-Cu eutectic+Cu(s,s)/Cu(s,s)/Cu(s,s)+Ag-Cu eutectic/Cu3Ti+TiN/Si3N4 ceramics. With the increasing of the brazing temperature, four-point bending stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Si 3 N 4 has been joined to steel, 7,8 aluminides, 3 tungsten (W), titanium (Ti), and niobium (Nb), 9,10 Ni‐base superalloys, 11–15 and other substrates using either direct bonding or in combinations of metal interlayers 16–18 . For example, multilayered Si 3 N 4 /steel joints have been brazed using AgCuTi brazes in conjunction with 2–4 mm thick Ni/W/Ni interlayers for applications such as turbocharger rotors with a Si 3 N 4 disc brazed to a steel shaft 1 …”
Section: Introductionmentioning
confidence: 99%
“…Si 3 N 4 has been joined to steel, 7,8 aluminides, 3 tungsten (W), titanium (Ti), and niobium (Nb), 9,10 Ni‐base superalloys, 11–15 and other substrates using either direct bonding or in combinations of metal interlayers 16–18 . For example, multilayered Si 3 N 4 /steel joints have been brazed using AgCuTi brazes in conjunction with 2–4 mm thick Ni/W/Ni interlayers for applications such as turbocharger rotors with a Si 3 N 4 disc brazed to a steel shaft 1 …”
Section: Introductionmentioning
confidence: 99%
“…Studying amorphous brazing solders, Rabinkin et al of U.S. United Signal Corporation have found that little eutectic exists in the central area of the brazed joint of an amorphous brazing filler metal, and only a small amount of discontinuous chromium-boron compound exists at the interface with the base metal. Therefore, the strength of the brazed joint is high [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to uneven heating in the welding process, the temperature gradient in the surfacing welding process is large, leading to high welding stress, deformation, and even cracking. The strengthening thickness of gas-phase deposition coatings is relatively thin [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%